The Effect of Financial Management Comprehension, Financial Accounting System, and Internal Supervision on Financial Report Performance Province Government of North Sumatra - Rizty Fanny Novriyanti; Renny Maisyarah; Nina Andriany Nasution (Sean Institute, 2025)
The increasing demands of society for good governance have encouraged the central government and local governments to implement public accountability. In order to realize good governance, local governments must continue to make efforts to improve transparency and accountability in regional financial management. This study aims to determine whetherunderstanding of financial management, financial accounting systems and internal supervisors have a simultaneous effect on the financial statements of the North Sumatra Provincial Government. The type of research used is by using a quantitative method assisted by SPSS 23. The population and sample in this study were 60 Civil Servants in the North Sumatra Provincial Government and questionnaires were distributed according to the number of samples that had been determined. This study found that there was a positive and significant relationship between Understanding of Financial Management and Financial Report Performance, the Financial Accounting System had a positive and statistically significant effect on Financial Report Performance, Internal Supervision had a negative and statistically significant relationship on Financial Report Performance that excessive or inefficient internal supervision also has the potential to inhibit flexibility and innovation, which in turn can affect financial performance.